2004
DOI: 10.1111/j.1600-0854.2004.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Covert Operations of Uropathogenic Escherichia coli within the Urinary Tract

Abstract: Entry into host cells is required for many bacterial pathogens to effectively disseminate within a host, avoid immune detection and cause disease. In recent years, many ostensibly extracellular bacteria have been shown to act as opportunistic intracellular pathogens. Among these are strains of uropathogenic Escherichia coli (UPEC), the primary causative agents of urinary tract infections (UTIs). UPEC are able to transiently invade, survive and multiply within the host cells and tissues constituting the urinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
140
0
14

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(154 citation statements)
references
References 117 publications
(178 reference statements)
0
140
0
14
Order By: Relevance
“…By hindering host cytokine expression and ensuing inflammatory responses, UPEC may be better able to establish itself and multiply within the cells and tissues of the urinary tract. At the same time, UPEC-induced death of bladder and renal epithelial cells can compromise mucosal barriers, and it may thereby facilitate bacterial dissemination and persistence within the urinary tract (Mulvey et al, 1998Chen et al, 2003a;Bower et al, 2005;Eto et al, 2006;Mansson et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By hindering host cytokine expression and ensuing inflammatory responses, UPEC may be better able to establish itself and multiply within the cells and tissues of the urinary tract. At the same time, UPEC-induced death of bladder and renal epithelial cells can compromise mucosal barriers, and it may thereby facilitate bacterial dissemination and persistence within the urinary tract (Mulvey et al, 1998Chen et al, 2003a;Bower et al, 2005;Eto et al, 2006;Mansson et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…By hindering host cytokine expression and ensuing inflammatory responses, UPEC may be better able to establish itself and multiply within the cells and tissues of the urinary tract. At the same time, UPEC-induced death of bladder and renal epithelial cells can compromise mucosal barriers, and it may thereby facilitate bacterial dissemination and persistence within the urinary tract (Mulvey et al, 1998Chen et al, 2003a;Bower et al, 2005;Eto et al, 2006;Mansson et al, 2007b).A key regulator of host cell survival pathways is Akt (also known as protein kinase B, PKB; for recent reviews, see Fayard et al, 2005;Song et al, 2005;Manning and Cantley, 2007). This serine/threonine kinase is able to inhibit apoptosis, and it can help control cell cycle and metabolic pathways, endocytosis and vesicular trafficking, and host inflammatory responses, including the activation of NF B. Akt is activated downstream of phosphoinositide 3-kinase (PI3-kinase), which itself is activated by integrin signaling, the engagement of G protein-coupled receptors, or the stimulation of receptor tyrosine kinases by insulin or other growth factors (Vanhaesebroeck et al, 2001).…”
mentioning
confidence: 99%
“…Traditionally, UPEC strains were considered strictly extracellular pathogens. However, more recent work has demonstrated that UPEC can invade the epithelial cells that line the lumenal surfaces of the urinary tract (7). In mouse UTI models, intracellular UPEC have a notable survival advantage over their extracellular counterparts, and are able to persevere within the urinary tract for extended periods in the face of robust innate host defenses and even antibiotic treatments (3, 8 -13).…”
mentioning
confidence: 99%
“…Međutim, bakterije mogu da izbegnu ove odbrambene mehanizme i da u epitelnim ćelijama formiraju grupice u obliku grozdova u kojima su zaštićene i mogu predstavljati rezervoare nedostupne odbrambenim mehanizmima [12][13][14]. Značaj ovih intraćelijskih rezervoara za nastanak rekurentnih infekcija opisan je u eksperimentalnim modelima, ali njihova uloga nije potvrđena u humanim rekurentnim infekcijama [15][16][17].…”
Section: Infekcija Mokraćnih Puteva -Primer Interakcije Domaćin-mikrunclassified